Structural and Functional Plasticity at the Axon Initial Segment - Yamada, Rei; Kuba, Hiroshi (Frontiers in Cellular Neuroscience, 2016)
The axon initial segment (AIS) is positioned between the axonal and somato-dendritic compartments and plays a pivotal role in triggering action potentials (APs) and determining neuronal output. It is now widely accepted that structural properties of the AIS, such as length and/or location relative to the soma, change in an activity-dependent manner. This structural plasticity of the AIS is known to be crucial for homeostatic control of neuronal excitability. However, it is obvious that the impact of the AIS on neuronal excitability is critically dependent on the biophysical properties of the AIS, which are primarily determined by the composition and characteristics of ion channels in this domain. Moreover, these properties can be altered via phosphorylation and/or redistribution of the channels. Recently, studies in auditory neurons showed that alterations in the composition of voltage-gated K+ (Kv) channels at the AIS coincide with elongation of the AIS, thereby enhancing the neuronal excitability, suggesting that the interaction between structural and functional plasticities of the AIS is important in the control of neuronal excitability. In this review, we will summarize the current knowledge regarding structural and functional alterations of the AIS and discuss how they interact and contribute to regulating the neuronal output.